(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
Enlightened absolutism represents a state policy which is implemented by the European forces in the duration of the 18th century. The chronological line of the enlightened absolutism covers the period of almost a half of century, from 1740 until 1789 i.e. to the start of the French revolution. The enlightened absolutism is a movement within the absolutism which follows after autocracy (fascism) and precedes the despotism. As founder and ideologist of the Enlightened absolutism is considered Thomas Hobbes with his master piece the Leviathan. The Leviathan according to Hobbes is a sovereign state power (the best form for him is absolute monarchy), which is needed in order to compel people of their obligations. The philosophy of this policy amounts to postulate which stipulates that the social reforms are possible but only through the state and for the state, this phenomena are social expression of the state interest and the state is the only possible protector of fundamental rights and freedoms of the man and the citizen is the state. In other words, according to the Enlightened absolutists (adherents of the absolute monarchy) ‘welfare in society “is possible only and only through the state and the regime that was established by the same. Because of all above mention, our interest in this paper is to explain the basic goal of the ideas of the enlightened absolutism.